Study of fisherman income and affecting factors (study in South Halmahera) - Prince Charles Heston Runtunuwu; Erlambang Budi Darmanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
The objectives of this study is to analyze the direct effect of the amount of catch on fish prices and fishermen's income, operational costs on fish prices and fishermen's income, fish prices on fishermen's income, the amount of catch, operational costs and to on fishermen's income through fish prices. The analytical method used in this research is path analysis using the SPSS program as a statistical test tool. The results of this study indicate that: (1) the amount of catch has a positive and significant effect directly on the amount of catch and has a positive and significant effect directly on the income of fishermen. (2) Operating costs have a positive and significant effect directly on fish prices and fishermen's income. (3) Fish prices have a positive and significant direct effect on fishermen's income.(4) The number of fishermen's catch has a positive effectindirectly to fishermen's income through fish prices. (5) Operational costs have an indirect negative effect on fishermen's income through fish prices.Keywords:CostDevelopmentEconomicFisheryPath Analysis